Influence of leaf dry mass per area, CO₂, and irradiance on mesophyll conductance in sclerophylls - Hassiotou, Foteini; Ludwig, Martha; Renton, Michael; Veneklaas, Erik J; Evans, John R (Journal of experimental botany, 2009)
Leaf photosynthesis (A) is limited by mesophyll conductance (gm), which is influenced by both leaf structure and the environment. Previous studies have indicated that the upper bound for gm declines as leaf dry mass per area (LMA, an indicator of leaf structure) increases, extrapolating to zero at a LMA of about 240 g m⁻². No data exist on gm and its response to the environment for species with LMA values higher than 220 g m⁻². In this study, laboratory measurements of leaf gas exchange and in vivo chlorophyll a fluorescence were used concurrently to derive estimates of gm in seven species of the Australian sclerophyllous genus Banksia covering a wide range of LMA (130-480 g m⁻²). Irradiance and CO₂ were varied during those measurements to gauge the extent of environmental effects on gm. A significant decrease of gm with increasing LMA was found. gm declined by 35-60% in response to increasing atmospheric CO₂ concentrations at high irradiance, with a more variable response (0-60%) observed at low irradiance, where gm was, on average, 22% lower than at high irradiance at ambient CO₂ concentrations. Despite considerable variation in A and LMA between the Banksia species, the CO₂ concentrations in the intercellular air spaces (Ci, 262±5 μmol mol⁻¹) and in the chloroplasts (Cc, 127±4 μmol mol⁻¹) were remarkably stable.